Florida Birds : A Birdwatcher Discovers the Sunshine State - Janes, Ken, 1942- (Palm Beach, Florida : Pineapple Press, 2024)
"Wading birds, raptors, waterfowl, pelicans, gulls & terns, shorebirds, and songbirds. These are the types of birds Florida birdwatchers can see and learn about in Ken Janes' stunning photobook Florida Birds: A Birdwatcher Discovers the Sunshine State. With all original photography by Janes and informational sections for each bird listed, those interested in the year-long hobby of Florida birdwatching will be able to not only learn key facts from this book but also display it in their homes as a piece of photo art"--
Keywords: Birds -- Florida -- Identification